Improving contemporary outcomes following heart transplantation for cardiac amyloidosis. Issue 10 (12th July 2021) - McGoldrick, Matthew T.; Etchill, Eric W.; Giuliano, Katherine; Barbur, Iulia; Yenokyan, Gayane; Whitman, Glenn; Kilic, Ahmet
Abstract: Background: The incidence of systemic amyloidosis is rising, and there is a concomitant rise in heart transplant for an indication of cardiac amyloidosis. Methods: We utilized the Organ Procurement and Transplantation Network (OPTN) database to retrospectively assess survival and outcomes in adult patients undergoing heart transplant for cardiac amyloidosis from 1999 to 2019. We also compared survival among four distinct time periods: 1999–2001, 2002–2008, 2008–2015, 2016–2019. Results: Of 41, 103 patients, 425 (1.03%) were transplanted for an indication of restrictive cardiomyopathy due to cardiac amyloidosis (RCM‐Amyloidosis). The percent of all transplants occurring for RCM‐Amyloidosis increased from 0.25% in the 1999–2001 era to 1.74% in the 2015–2019 era ( p < .001). Across eras, Kaplan–Meier survival functions were comparable between RCM‐Amyloidosis and non‐RCM patients at 1 year (88% vs. 89%, p = .56) and at 5 years (72% vs. 77%, p = .092), but worse for RCM‐Amyloidosis patients at 10 years (44% vs. 59%, p = .002). With adjustment for other clinical variables in multivariable Cox regression model, RCM‐Amyloidosis was not associated with increased risk of death at 1 year (hazard ratio [HR] = 1.11, p = .56) or at 5 years (HR = 1.20, p = .18), but it was associated with increased risk of death at 10 years (HR = 1.35, p = .01). Cardiac amyloidosis was not associated with any morbidity outcomes following transplant, including graft failure, acute rejection, or hospitalization for infection or rejection. Conclusions: Our data suggest a trend of improving survival among RCM‐Amyloidosis patients compared with non‐RCM patients across transplant eras, with current similarities in 1‐ and 5‐year survival but a persistent, increased risk of mortality at 10 years.